Experimental comparison among Fast Block Matching Algorithms (FBMAs) for motion estimation and object tracking - Hashimaa, Sherief M.; Mahmoud, Imbaby I.; Elazm, Atef A. (2011 28th National Radio Science Conference, 2011)
In this paper two different Fast Block Matching Algorithms (FBMAs) are introduced and analyzed. They are One Point Pentagon Inner Search (OPPEN) and Predicted One Point Hexagon Inner Search (POPHEX) algorithms. The proposed algorithms are compared with other FBMAs like Diamond Search (DS), and Hexagonal based search (HEX) algorithms using MATLAB environment. The comparison is conducted for both motion estimation and object tracking using group of known test video sequences. The results showed that the proposed OPPEN algorithm has the best performance in terms of complexity and average cost function. Also it have the smallest tracking time consumption.